TIGER GAME AND THE DANGERS OF GAMBLING ADDICTION - dos Reis, Rosane Pereira; da Silva Machado, Mickaelly; Calheiros, Renée Leão; Nicácio, Otacylio Fernando Marinho Rodrigues; Figueiredo, Thales José Macedo; de Carvalho Mourão, Ana Raquel; Barreto, Daniela Martins Lessa; Bezerra, Daniele Gonçalves (Seven Editora, 2025)
Betting addiction is a complicated phenomenon that encompasses psychological, social, and biological aspects. The "Tigrinho Game", a famous gambling entertainment, has aroused the interest of scholars and health experts because of its great potential to lead to addictive behaviors. This study aimed to describe through scientific evidence the impact of tiger game on gambling addiction, as well as the possible psychological, social and economic consequences. This is an integrated literature review study, covering articles from the years 2020 to 2025, and using data sources such as Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO) and Pubmed. From these results it was possible to observe that addiction to gambling is linked to several elements, such as heredity, environmental influences and the nature of the gaming industry, such as the tiger game, which employs psychologically attractive tactics to increase participation. It is therefore concluded that the Tiger Game serves as a clear example of how addictive gambling can become. Intervention strategies need to incorporate therapeutic methods, awareness campaigns in public policies and the regulation of gaming.DOI: https://doi.org/10.56238/sevened2025.029-041